Identification of Ohmic Stator Resistance Based on Low Frequency Current Signal Injection in Permanent Magnet Synchronous Machines - Kellner, Sven; Piepenbreier, Bernhard (EPE-PEMC 2010, 2010)
This paper introduces a novel approach to identifying the ohmic stator resistance Rs of permanent magnet synchronous machines (PMSM) based on low frequency signal injection. The identification does not depend on specific speed or load conditions. Besides the value of Lq(id, i q), no further electrical parameter is needed for the identification algorithm. The proposed stator resistance identification method is verified by two test benches. One contains an internal permanent magnet synchronous machine (IPMSM) the other a PMSM with surface-mounted permanent magnets. Each test bench has a dc machine as load. The IPMSM especially shows extensive harmonic effects. So an adequate filtering approach for the measured input values of the proposed identification algorithm is presented. © 2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.identi
Keywords: Adjustable speed drive; Control of drive; Drive electrical drive; Electrical machine; Permanent magnet motor variable speed drive